Hematomas in Tiger Territory: An Endovascular Alternative to Wading In. Issue 6 (November 2017) - Teso, Desarom; Rogoway, Benjamin J.; Vea, Yolanda L.; Threlkeld, Judson E.; Dulabon, George R.; Karmy-Jones, Riyad C.
A 26-year-old man presented with gunshot wound to the epigastrium. At surgery, he was hemodynamically stable and had a tense hematoma with thrill in zone 2 (right side) and porta triad. After liver injury was controlled, he underwent percutaneous stenting of a renal artery-vena cava fistula and the hepatic artery injury was followed. Historically, penetrating injury to zone 2 has mandated operative exploration. However, with the advent of endovascular options, in stable patients, catheter-based options offer a reasonable alternative with less risk of blood loss and possible nephrectomy. Renal artery stenting has been advocated for renal artery cava fistulas. The role of timing, hybrid operating suites, and traditional operative exposure will vary based on presentation and institutional capabilities.